Strategi Reengineering di Perusahaan Manufaktur untuk Meningkatkan Daya Saing di Era Industri 4.0: Studi Literatur tentang Penerapan Teknologi Informasi dan Inovasi - Warih, Wido Cepaka; Aurellia, Miranda; Simanjuntak, Davit Lungguk; Azka, Aqori Satria; Putra, Erwin Aditya (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2024)
Reengineering is a radical process to redesign existing business processes with the aim of enhancing performance, quality, and efficiency. Reengineering can assist manufacturing companies in adapting to the challenges and opportunities in the era of Industry 4.0, characterized by digitization, automation, and system integration. This article aims to examine the reengineering strategies of manufacturing companies in the Industry 4.0 era, focusing on the implementation of information technology and innovation. The research method utilized is literature review, which involves collecting, analyzing, and synthesizing information from various relevant sources such as journal articles, books, reports, and websites. The research findings indicate that reengineering in manufacturing companies in the Industry 4.0 era involves several steps: (1) identifying and understanding existing business processes and customer needs; (2) determining the vision, mission, and objectives of reengineering; (3) redesigning business processes utilizing information technology and innovation, such as the Internet of Things, cloud computing, big data, artificial intelligence, machine learning, robotics, and 3D printing; (4) implementing new business processes involving all stakeholders, including employees, management, suppliers, and customers; and (5) evaluating and monitoring the performance and impact of reengineering. This article also discusses some of the benefits, challenges, and critical success factors of reengineering manufacturing companies in the Industry 4.0 era